PENGARUH DIMENSI DIMENSI IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH PROVINSI NUSA TENGGARA BARAT - Muhammad Amri Fuadi; Hermanto Hermanto; Lalu Suparman (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
This research is directed to prove the significance of the influence of organizational climate dimensions in the form of physical environment (X1), social environment (X2) and management system (X3) on the dimensions of employee performance in the form of employee work goals (Y1) and employee work behavior (PKP). There are six hypotheses that are proven through a partial least square (PLS) analysis process. The population of this study (observation data) was 82 BKD NTB employees. Data was collected through questionnaires and all questionnaires returned in accordance with data input needs. Through the outer model stage there are two indicators of the social environment that are issued, namely the relationship of superiors with subordinates (LS1) and colleague relations (LS2) as well as two indicators of employee work behavior, namely commitment (PKP3) and leadership (PKP6). Indicators that are classified as valid get a reinforcement of criteria through the parameter AVE values above 0.50 and include reliable indicators through Cronbach's alpha parameters and composite reliability above 0.70. PLS analysis through the inner model stage found that all dimensions of the organization's climate have a positive influence (positive sign of the path coefficient) on the dimensions of employee performance.Keywords : Organizational Climate Dimensions and Employee Performance Dimensions.